Does indexation bias the estimated frequency of price adjustment? - Maral Kichian; Oleksiy Kryvtsov (Bank of Canada, 2007)
We assess the implications of price indexation for estimated frequency of price adjustment in sticky price models of business cycles. These models predominantly assume that non-reoptimized prices are indexed to lagged or average inflation. The assumption of price indexation adds tractability although it is not likely reflective of the price practices of firms at the micro level. Under indexation firms have less incentive to adjust their prices, which implies downward bias in the estimated frequency of price changes. To evaluate the bias, we generate data with Calvo-type models without indexation. The artificial data are then used to estimate the frequency of price changes with indexation. Considering different assumptions about the degree of price rigidity and the level of trend inflation in the data-generating model, we find that the estimated indexation bias can be substantial, ranging up to 12 quarters in some cases.
Keywords: E31; E37; 330; Inflation and prices; Economic models; Econometric and statistical methods; Indexierung; Betriebliche Preispolitik; Inflationsrate; Konjunktur; Preisrigidität; Wirtschaftsmodell